Corneal surface wettability and tear film stability before and after scleral lens wear. Issue 5 (October 2019) - Serramito, Maria; Privado-Aroco, Ana; Batres, Laura; Carracedo G, Gonzalo
Highlights: Scleral lens wear improves subjective vision and comfort after one month of wearing. The tear film surface quality is worse after contact lens wearing in keratoconus patients. Subjective vision and comfort improved after one month of scleral lens wear. Abstract: Purpose: The aim of this study was to evaluate the anterior surface of scleral contact lens and ocular surface wettability before and after one-month of scleral lens wear in patients with keratoconus. Methods: Forty-nine patients with keratoconus (36.26 ± 9.03 years) were recruited. The sample was divided into two groups: patients with intrastromal corneal ring (KCICRS group) and patients without ICRS (KC group). TFSQ, Schirmer I test, Ocular Surface Disease Index (OSDI questionnaire), tear break-up time (TBUT) and corneal staining were evaluated in two different visits: Baseline (before lens wear) and one-month visit (10 min after lens removal). Visual Analog Scale (VAS questionnaire) was filled in just after inserting the lenses and just before removing them. TFSQ mean and inferior were evaluated over the contact lens surface at the moment of inserting the lens (baseline visit) and after 8 h of lens wear (one-month visit). Results: Anterior corneal surface TFSQ values increased in all groups after scleral lens wear (p < 0.05). However, there were no statistical differences found at the moment of inserting or after 8 h of lens wear on previous contact lens surface TFSQ (p > 0.05). No changes were found in tear volume for total and in KC and KCICRS groups (p > 0.05). For all groups, there was a statistical decrease of TBUT (p < 0.05). In addition, OSDI score, corneal staining and VAS score improved after scleral lens wear from baseline in total and in both KC and KCICRS groups (p < 0.05). Conclusion: The scleral contact lens surface keeps its wettability after one-month of wear. However, the wettability of the ocular surface is worse after contact lens wearing.